Structural Phenomena as Agents of Text Expression in a Pair of Songs from Schumann’s Liederkreis, Op. 39 - J. Randall Wheaton (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2014)
In the great store of masterful songs that came from the pen of Robert Schumann (1810–56) is his second song cycle entitled Liederkreis (op. 39, the first one being op. 24), a particularly rich trove of innovative settings of poems by Joseph Eichendorff (1788–1857). Composed in 1840, Schumann’s so-called year of song and the year that he married the virtuoso pianist Clara Wieck (1819–96), these works have not received the degree of scholarly attention, and particularly not the level of analytical focus, that they really deserve. An exception would be the startling and tonally problematic setting of “Auf einer Burg,” the seventh song in the cycle and the centerpiece of an eponymous essay that appeared as a chapter in David Lewin’s posthumous Studies in Music with Text (Oxford University Press, 2006). Lewin’s thesis, in brief, is that this song has an E-Phrygian Urlinie and that it ends with “a perfectly static tonic, requiring no further action whatsoever.” The present author’s analysis stands in direct opposition to this provocative view and posits a hearing that demands a structural coupling between this piece and the following song, “In der Fremde.” (Lewin anticipates this possibility but remains obdurately skeptical.) In particular, this article documents that an array of motivic, harmonic, and structural forces is so compelling that, the author holds, few tonal listeners could hear the first song as a strictly individuated work. Moreover, the analysis reveals that a feature critical to this perception is that “Auf einer Burg,” while still governed by tonal principles, is aberrant to the extent of lacking a traditional background. The resulting discussion amounts to a kind of analytical dialog between Lewin’s hearing and the author’s own. Besides presenting a complete Schenkerian analysis of both songs, the article demonstrates that text painting and motives in these pieces transpire not only on the musical surface but also on deeper levels of musical structure. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part V).